Expression of hemidesmosomal and extracellular matrix proteins by normal and malignant human prostate tissue. - Nagle, R. B. (1995)
The progression of prostate carcinoma may be influenced by the biochemical nature of the basal lamina surrounding the primary carcinoma cells. As a first step toward understanding this process, the composition and structure of the basal lamina in normal prostate, prostatic intraepithelial neoplasia, and human carcinoma were determined. In addition, a comparison was made between the attachments of the normal basal cell to its underlying basal lamina and those made by primary prostate carcinoma. The normal basal cells form both focal adhesions and hemidesmosomal-like structures as observed by transmission electron microscopy. The normal basal cells exhibited a polarized distribution of hemidesmosomal associated proteins including BP180, BP230, HD1, plectin, laminin-gamma 2(B2t), collagen VII, and the corresponding integrin laminin receptors alpha 6 beta 1 and alpha 6 beta 4. The expression and distribution pattern of these proteins were retained in the prostate intraepithelial neoplasia lesions. In contrast, the carcinoma cells uniformly lacked hemidesmosomal structures, the integrin alpha 6 beta 4, BP180, laminin-gamma 2 (B2t), and collagen VII but did express BP230 (30%), plectin, HD1 (15%), and the integrin laminin receptors alpha 3 beta 1 and alpha 6 beta 1. These results suggest that, although a detectable basal lamina structure is present in carcinoma, its composition and cellular attachments are abnormal. The loss of critical cellular attachments may play a role in influencing the progression potential of prostate carcinoma.